2015
DOI: 10.1002/ett.2949
|View full text |Cite
|
Sign up to set email alerts
|

Delay‐aware resource control for device‐to‐device underlay communication systems

Abstract: In this paper, we study delay‐aware resource control in device‐to‐device underlay communication systems with multiple source‐destination pairs. With the consideration of random bursty arrivals and delay‐sensitive information flows, cross‐layer optimization seeks to develop algorithms that (i) provide efficient throughput‐utility, (ii) are robust to general time‐varying conditions and (iii) guarantee bounded worst‐case delay. To deal with the delay constraints, both the large deviation approach and the Lyapunov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In the literature, combining the information theoretical bounds and queuing dynamics has been done either by converting a latency constraint into an equivalent rate constraint [6] or relying on elimination [7] or minimization [8] of the interference. In [6], a delay aware resource allocation problem was defined as a sum throughput maximization problem and two statistical approaches were used for expressing a delay constraint in terms of physical layer parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, combining the information theoretical bounds and queuing dynamics has been done either by converting a latency constraint into an equivalent rate constraint [6] or relying on elimination [7] or minimization [8] of the interference. In [6], a delay aware resource allocation problem was defined as a sum throughput maximization problem and two statistical approaches were used for expressing a delay constraint in terms of physical layer parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, combining the information theoretical bounds and queuing dynamics has been done either by converting a latency constraint into an equivalent rate constraint [6] or relying on elimination [7] or minimization [8] of the interference. In [6], a delay aware resource allocation problem was defined as a sum throughput maximization problem and two statistical approaches were used for expressing a delay constraint in terms of physical layer parameters. In the first approach, a large deviation theory was used to convert the delay constraint into the equivalent rate constraint and in the second approach the characteristics of the power control policies was analyzed by using Lyapunov drift stochastic stability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The work in the study of Cui et al (2012) was used (Li et al, 2017) for the latency analysis of the D2D pairs, and is concluded that D2D pairs latency depends on the order of data arrival and type. Another approach named Stochastic majorization is used in Asheralieva and Miyanaga (2016) that implements the longest queue highest rate possible approach for providing a power control, which is latency aware.…”
mentioning
confidence: 99%